Adsorção de molibdato em minerais de argilas naturais e modificadas com ácido sulfúrico, ácido húmico e uréia - PEREIRA, Patrícia Magalhães (2015)
Clay sediments from the municipalities Assis Brazil (Acre), were leached with solutions of sulfuric acid, humic acid and urea, to evaluate the retention capacity of molybdate in these materials and to investigate the feasibility of the adsorption processes at solid-solution interfaces. The materials were characterized from data of XRD, FTIR spectra, surface charge and chemical composition. The Langmuir isotherm models, Freundlich and Sips were used to fit the experimental data of adsorption. The minerals identified in the clay sediments were smectite, kaolinite, illite, quartz, albite, calcite and microclineo. The chemical modification leads amorphization of the modified sample with sulfuric acid and delamination along the plane 001 of the modified sample with urea. The settings defined by mathematical parameters (KL,Kf) of the adsorption isotherms, evaluation Ce vs. qe, pH vs. Qe, Qmax (sips) and Kd, indicated that the S10H15 sample is more efficient in the adsorption MoO42- ,with com qMax = 6.83 mg. L-1.